“Killing All Infidels”: Leaking Prior to Islamist Terrorist Attacks in Germany - Tampe, Laura (Terrorism and political violence, 2025)
Leaking includes observable statements, offense-related behaviors, and an interest in similar offenses prior to severe targeted violence, making it a crucial starting point for the prevention of Islamist attacks. Most studies to date only examined the frequency of leaking, used a narrow definition, and based on open source data. Thus, little is known about its contents, trajectories, and assessment criteria. We analyzed the prosecution files of 27 Islamist attacks in Germany (48 offenders) and of 52 individuals that showed leaking, but did not execute an attack (comparison group). Leaking was shown by 96 percent of the offenders, often repeatedly and over an average period of one year. Most leaked face-to-face, via observable behavior, or in chats. Leakings rarely included details of the planned attack, but rather signaled an interest in similar attacks/terrorism and the preparation of an attack. Over time, leaking became more closely offense-related, indicating a pathway to an attack. Leaking differed significantly between offenders and the comparison group in contents and characteristics that were combined into the risk assessment tool LATERAN-IT that assesses the seriousness of Islamist-motivated leaking. Hence, leaking allows for the identification of potential Islamist terrorists in advance, so that law enforcement authorities can prevent future attacks.